Eksplorasi peran Customer Brand Engagement dalam Berlangganan Streaming - Frisilia Tirto; Joel Faruk Sofyan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
As the digital era develops, providing digital content has become an increasingly popular business model, one of which is Netflix, where users can access digital content easily anytime and anywhere. Pass time, utility, and interesting entertainment are factors that contribute to increasing customer brand engagement which also has an influence on brand image and purchase intention. The aim of this research is to analyze the influence of customer brand engagement on brand image and purchase intention. Data collection was carried out using an online survey using purposive sampling technique and using 150 selected respondents. The data is then processed by applying PLS-SEM to test the proposed hypothesis. Research findings reveal that utility, pass time and entertainment can increase customer brand engagement. Meanwhile, customer brand engagement can increase brand image and purchase intention. Brand image can also increase purchase intention. Furthermore, utility and pass time can increase customer brand engagement mediated by entertainment. The implications of this research provide a strong basis for Netflix management in preparing marketing plans to focus on improving customer experience by providing appropriate content and developing brand image through appropriate marketing strategies so as to increase purchasing intentions..